ASSOCIATION OF SMOKING WITH RECURRENCE OF PULMONARY KOCHS; AFTER COMPLETION OF ANTITUBERCULOUS TREATMENT - Ahmad, Darakhshan; Khan, Muhammad Mujeeb; Aslam, Faiza; Abbas, Sundas; Elahi, Qurrat-ul-ain (Journal of Ayub Medical College Abbottabad, 2016)
Background: Smoking is one of the most important yet modifiable risk factors for incidence, morbidity, recurrence and mortality from Pulmonary Koch’s or tuberculosis. This study attempted to demonstrate the association between smoking and recurrence risk of Pulmonary Koch’s in Pakistani male population. Methods: This case control study was conducted at Federal Government Tuberculosis Hospital, Rawalpindi from 2015 to 2016. It included 332 study participants; 166 recurrent cases of Pulmonary Tuberculosis within two years of completion of Anti-tuberculous therapy (ATT) and 166 non-recurrent controls. Smoking status of all study participants was assessed. Results: Amongst 166 cases of recurrence, 75 (63.6%) had continued smoking after ATT compared to 43 (36.4%) controls who continued smoking (p-value 0.00, OR=2.35, 95% CI=1.48 to 3.74, NNH=4.75). Highly statistically significant associations of recurrence were observed with smoking>10 years (p-value 0.00, OR=3.67, CI=1.55-8.71 NNH=4.75) and if ever smoked in life (p-value 0.00, OR=2.05, CI=1.32-3.19, NNH=5.61). Mean duration of smoking in cases (12.37±8.72 years) was statistically different from controls (9.54±7.01 years), with p-value of 0.04. Conclusion: There is strong association of recurrence of Pulmonary Kochs with continuation of smoking within 2 years of completion of ATT, with ever smoking in life and smoking >10 years in life. Keywords: Pulmonary; Tuberculosis; Smoking; Cigarette smoking; Recurrence